Teachers' perceptions of the barriers of employing educational technology skills in teaching - S. Ya. Rababa'h; L. M. Rababah; M. A. Rababah; M. G. Bany Hani; O. I. Alorani; F. A.M. Al-Habies (Russian State Vocational Pedagogical University, 2024)
Introduction. The development of technologies in the context of the formation of the sixth technological order provides new tools and methods for educational institutions, significantly simplifying the acquisition of knowledge by students. Aim. This study aimed to investigate teachers' opinions on the challenges associated with the integration of new educational technologies into the educational process. Methodology and research methods. As the primary method, a quantitative approach using a descriptive questionnaire study was employed to investigate the issues related to teachers' motivation and their proficiency in utilising new educational technologies in the educational process. The study involved a participant group of 144 teachers from Irbid, Jordan. Results. The results indicated that the technological competence of teachers did not significantly impact the efficiency of technology use. This is attributed to the fact that nearly all teachers have received adequate training, possess the necessary tools, and extensively apply technical knowledge in their work. Nevertheless, problems related to the state of educational institutions' infrastructure persist. It has been established that educators are constantly striving to use innovative methods to create an ideal learning environment for their students. Their motivation serves as a driving force that determines their actions in the educational process and contributes to a targeted approach to task performance. At the same time, statistically significant gender differences were observed in favour of female teachers, as well as statistically significant differences in favour of teachers with a scientific specialisation and less than eight years of experience. The relevance of the study lies in its focus on teachers' technological abilities and how modern technologies are utilised in the classroom. Scientific novelty. Approaches have been developed to create effective strategies and teaching methods for the active integration of new educational technologies in educational institutions in Jordan. Practical significance. The proposed solutions to enhance the utilisation of educational technologies by teachers can be adopted by educators from various countries to enhance their technological skills throughout the educational process.